2018
DOI: 10.1007/s10899-018-9773-z
|View full text |Cite
|
Sign up to set email alerts
|

Losses Disguised as Wins Affect Game Selection on Multiline Slots

Abstract: Multiline slots are exciting games that contain features which make them alluring. One such feature is a loss disguised as a win (LDW); wherein, players win less than they wager (e.g., bet 2 dollars, win back 50 cents), but this net loss is disguised by flashing graphics and winning sounds. Research to date concludes that LDWs are both rewarding and reinforcing. Here, we investigated whether LDWs affect players’ game selection. Thirty-two undergraduate students with experience playing slot machines played 100 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
2
4
0
Order By: Relevance
“…A similar, albeit stronger, pattern was observed following clear wins. This result is broadly consistent with behavioral and self‐report findings that participants prefer to gamble on multiline slots that present LDWs relative to machines that do not (Graydon et al., 2018), as well as observations based on user account data by Leino et al. (2016) that consumers were more likely to terminate a gambling session following a loss, relative to an LDW.…”
Section: Discussionsupporting
confidence: 87%
“…A similar, albeit stronger, pattern was observed following clear wins. This result is broadly consistent with behavioral and self‐report findings that participants prefer to gamble on multiline slots that present LDWs relative to machines that do not (Graydon et al., 2018), as well as observations based on user account data by Leino et al. (2016) that consumers were more likely to terminate a gambling session following a loss, relative to an LDW.…”
Section: Discussionsupporting
confidence: 87%
“…Behavioural experiments suggest that players prefer multiline slot machines that allow LDWs compared to single-line variants, or games that do not allow for LDWs (Delfabbro et al, 2005;Dixon et al, 2014a;Graydon et al, 2018). Interviews with regular slot machine players (Livingstone et al, 2008), analysis of actual play data (MacLaren, 2015;Templeton et al, 2015), and observation of play (Landon et al, 2017), suggest that players adjust their playstyles such that the probability of LDWs occurring is maximised.…”
Section: The Science Of Ldwsmentioning
confidence: 99%
“… Jensen et al, (2013) reported that LDWs were frequently mis-categorised as wins by a majority of research participants who were asked to verbally describe gambling outcomes aloud while under observation by experimenters. When offered a choice between EGMs that offer an equivalent expected financial return, but differ in the number of LDWs they produce, participants self-report a preference for, and are more likely to continue gamble using, machines that include LDWs ( Graydon et al, 2018 ). Consistent with LDWs being a salient outcome, a number of lab studies have also reported that LDWs elicit autonomic arousal in a manner comparable to small wins ( Dixon et al, 2010 , Wilkes et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%